Evaluatıon Of The Short Tıme Posttreatment Changes In The Mandıble In Open Bıte Cases Treated Wıth Dıfferent Treatment Mechanıcs - Müfide Dinçer; Lale Taner-Sarısoy; Hakan N. İşcan (Galenos Yayinevi, 2001)
The aim of this study is to compare the stabilization of the posttreatment mandibular changes obtained by vertical chin cup and posterior bite block in open bite cases in the short time retention period and the period where the appliances were not used. Skeletal open bite cases having Angle Class I or Class II division 1 malocclusions were included in the study. The retention period for nine subjects who had been treated by vertical chin cup was 9 months and it was 4 months for 13 subjects who had been treated by posterior bite blocks. The period where none of the appliances were used was 6 months for both groups. The assessments of the end of treatment, retention, and no appliance use periods were done by paired comparison-t test within the groups and by student-t test between the groups. In comparison of the two groups in the retention period, the changes in the SNB, SN/GoGn, ArGoM, and NGoM angles, and in the LMC⊥GOGn length in the no appliance use period were found to be significant. The sagittal development of the mandible continued in the retention period in subjects treated by vertical chin cup. The increase in the gonial angle and the vertical development in the lower posterior dentoalveolar structures were seen in subjects treated by posterior bite blocks. Therefore, the changes in the mandible obtained by vertical chin cup were found to be more stable, but it should be realized that the retention period was longer in this group.